Prevalence of iodine- and thyroglobulin negative findings in differentiated thyroid cancer - Klutmann, S.; Jenicke, L.; Geiss-Tönshoff, M.; Bohuslavizki, K. H.; Mester, J.; Clausen, M. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: The prevalence of iodine- and thyroglobulin-nega-tive findings was evaluated in all patients with differentiated thyroid cancer (DTC) treated from 1961 until 1998 at the Department of Nuclear Medicine, University Hospital Hamburg-Eppendorf. Methods: A total of 490 patients with papillary thyroid cancer (PCA) and 242 patients with follicular thyroid cancer (FCA) were analyzed retrospectively. Patients were divided into four groups: 1: no recurrence, 2: recurrent disease, 3: primary metas-tatic/progressive disease and 4: inconclusive follow-up. Results of iodine scan, serum-TG, and additional imaging modalities as well as histology were compared in all patients. Results: 21/490 (4,3%) of patients with PCA and 16/242 (6,6%) with FCA suffered from recurrent disease. 62/490 (12,7%) of patients with PCA and 59/242 (24,4%) with FCA had primary metastatic/progressive disease. 12/21 patients with PCA and 12/16 with FCA showing up with recurrent disease had a negative iodinescan. 11/21 of patients with PCA and 4/16 with FCA and tumor recurrence had negative serum-TG levels. 14/62 patients with PCA and 14/59 with FCA presenting with primary metastatic/ progressive disease had negative iodinescan. 14/62 patients with PCA and 6/59 with FCA had negative serum-TG. Conclusion: The prevalence of iodine-negative recurrent"/metastatic disease is in accordance to the literature, whereas the prevalence of TG-negative recurrent/metastatic was noted higher than reported previously. Thus, the commonly used follow-up scheme of DTC is confirmed. However, iodine scan should be regularly performed in patients with high risk of recurrence.
Keywords: Thyroid cancer; Recurrence; Metastases; Thyroglobulin; Iodine scan